2011
DOI: 10.1089/met.2011.0019
|View full text |Cite
|
Sign up to set email alerts
|

Higher Metabolic Risk with National Institutes of Health Versus Rotterdam Diagnostic Criteria for Polycystic Ovarian Syndrome in Turkish Women

Abstract: The NIH criteria identify women at high risk for insulin resistance and metabolic syndrome. The Rotterdam criteria include women who have less severe metabolic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
2
26
0
1
Order By: Relevance
“…Disagreement has persisted regarding whether the two additional phenotypes (oligo-ovulation with PCO or hyperandrogenism with PCOS) in Rotterdam criteria actually do have classical PCOS, because PCO on ultrasound is a very common finding in normal population [20]. Also in some studies they found that using NIH criteria predicts the metabolic risk more appropriately than Rotterdam criteria [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Disagreement has persisted regarding whether the two additional phenotypes (oligo-ovulation with PCO or hyperandrogenism with PCOS) in Rotterdam criteria actually do have classical PCOS, because PCO on ultrasound is a very common finding in normal population [20]. Also in some studies they found that using NIH criteria predicts the metabolic risk more appropriately than Rotterdam criteria [21]. …”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that metabolic features of PCOS differ across the diagnostic criteria with a higher prevalence of obesity and IR and worsened metabolic features reported for women diagnosed according to the NIH in comparison with the Rotterdam criteria. 41,42 However, this is not consistently demonstrated. A systematic review of adiposity in PCOS on 43 studies using NIH criteria and 63 studies using Rotterdam criteria 37 reported variable and broadly similar prevalence of overweight and obesity (NIH: 20%-100% vs Rotterdam: 5.9%-93.7%), obesity (14.3%-100% vs 12.5%-94.6%) and central obesity (49.3%-85.5% vs 20.0%-66.5%) across the diagnostic categories.…”
Section: Pcos Phenotypes and Adverse Pregnancy Outcomesmentioning
confidence: 92%
“…There is some evidence that metabolic features of PCOS differ across the diagnostic criteria with a higher prevalence of obesity and IR and worsened metabolic features reported for women diagnosed according to the NIH in comparison with the Rotterdam criteria . However, this is not consistently demonstrated.…”
Section: Possible Contributing Mechanisms Of Pcos In Adverse Pregnancmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were excluded if they had contraindications to fMRI, were pregnant within 6 months of the start of the study, had a history of substance abuse, used centrally acting medications or corticosteroids, or if they had used hormones within 2 months of the start of the study. We used the National Institutes of Health (NIH) criteria of menstrual irregularity and hyperandrogenism for the PCOS diagnosis because a higher metabolic risk has been seen with these diagnostic criteria (2, 15). Insulin resistance was defined as a homeostasis model assessment (HOMA2)–Glycemia (mmol/L) × Insulinemia ( μ IU/mL)/22.5–sensitivity of ≤60%.…”
Section: Methodsmentioning
confidence: 99%